"Asian Carp" is Societally and Scientifically Problematic. Let's Replace It. Issue 7 (27th July 2018) - Kočovský, Patrick M.; Chapman, Duane C.; Qian, Song
Abstract : Bighead Carp Hypophthalmichthys nobilis, Black Carp Mylopharyngodon piceus, Grass Carp Ctenopharyngodon idella, and Silver Carp H. molitrix are considered invasive species in North America and Europe. In North America, they are typically referred to collectively as "Asian carp, " a reference to their native range. The category "Asian carp" fails to acknowledge the cultural value and the ecological differences of these fishes, causes confusion when translated into Chinese, and frequently causes communication problems with the public and occasionally among professionals when some species are intentionally or inadvertently included or excluded when referred to collectively. Herein, we review the long history of aquaculture of these species in China, their human cultural significance, the origin of the category "Asian carp, " and the problems the term "Asian carp" might cause when used in cross‐cultural communication. We recommend discontinuing the use of this term and replacing it with individual species names. When a group term is required, there are several more favorable alternatives, including existing Chinese terms that have been used for centuries.